Docosahexaenoic Acid Induces Cell Death in Human Non-Small Cell Lung Cancer Cells by Repressing mTOR via AMPK Activation and PI3K/Akt Inhibition. (3rd August 2015) - Kim, Nayeong; Jeong, Soyeon; Jing, Kaipeng; Shin, Soyeon; Kim, Soyeon; Heo, Jun-Young; Kweon, Gi-Ryang; Park, Seung-Kiel; Wu, Tong; Park, Jong-Il; Lim, Kyu
Abstract : The anticancer properties and mechanism of action of omega-3 polyunsaturated fatty acids ( ω 3-PUFAs) have been demonstrated in several cancers; however, the mechanism in lung cancer remains unclear. Here, we show that docosahexaenoic acid (DHA), a ω 3-PUFA, induced apoptosis and autophagy in non-small cell lung cancer (NSCLC) cells. DHA-induced cell death was accompanied by AMP-activated protein kinase (AMPK) activation and inactivated phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling. Knocking down AMPK and overexpressing Akt increased mTOR activity and attenuated DHA-induced cell death, suggesting that DHA induces cell death via AMPK- and Akt-regulated mTOR inactivation. This was confirmed in Fat-1 transgenic mice, which produce ω 3-PUFAs. Lewis lung cancer (LLC) tumor cells implanted into Fat-1 mice showed slower growth, lower phospho-Akt levels, and higher levels of apoptosis and autophagy than cells implanted into wild-type mice. Taken together, these data suggest that DHA-induced apoptosis and autophagy in NSCLC cells are associated with AMPK activation and PI3K/Akt inhibition, which in turn lead to suppression of mTOR; thus ω 3-PUFAs may be utilized as potential therapeutic agents for NSCLC treatment.